Neighbourhood differences in retail turnover: Evidence from New York City - Meltzer, Rachel; Capperis, Sean (Urban studies (Edinburgh, Scotland), 2017)
Urban neighbourhoods are defined as much by their commercial character as their residential; retail services not only provide material needs for those living nearby, but less-tangible social and cultural capital as well. It is reasonable to expect, then, that excessive churn in these businesses can threaten the stability of a neighbourhood. Using a longitudinal data set on mixeduse neighbourhoods in New York City, we test whether or not neighbourhoods of varying circumstances and characteristics experience different degrees and types of retail turnover. Results suggest that there are meaningful differences in retail turnover across neighbourhoods. Retail turnover is directly associated with the type of business activity, commercial infrastructure and the neighbourhood’s consumer profile. However, when all three sets of factors are considered simultaneously in a regression analysis, consumer-related characteristics explain turnover more than those related to the local commercial environment. Specifically, businesses that provide necessity and more frequently consumed goods/services are more stable and chain establishments are more likely to venture into markets with some housing price discounts, growth potential and possibly less organised opposition. Neighbourhoods with less (and more heterogeneous) general retail (as opposed to food service) concentration, as well as bigger businesses, are more stable. More importantly, bigger households and higher shares of white residents are most strongly associated with less retail churn, and population growth is the strongest predictor of more turnover. 城市街区由它们的商业特征界定，也同样由它们的居住特征界定；零售服务不仅为附近居民提 供物质服务，也提供并不清晰可见的社会和文化资本。因此，可以合理预见，这些零售店的过 度流转会威胁街区的稳定。我们运用纽约市混合利用街区的一组纵向数据，测试了不同环境和 特征的街区是否会经历不同程度和类型的零售店流转。结果表明，不同街区在零售店流转方面 有着显著差异。零售店流转与业务类型、商业基础设施以及街区的消费者特征直接相关。但是， 通过回归分析来同时考虑这全部三组因素时，我们发现，相比与地方商业环境相关的特征，零 售店的流转更多与消费者相关的特征相关。具体而言，供应生活必需品和常用商品/服务的零售 店更稳定，连锁店更容易进入那些房价优惠、有增长潜力并且有组织的对抗较少的市场。一般 零售（与餐饮服务相对）集中度较低（更加异质化）的街区以及大型零售店聚集的街区，相比 之下更为稳定。更重要的是，房屋面积总体较大、白人居民占比较高的街区，其零售店流转率 往往更低，而人口增长是更高流转率的最强有力预测指标。